Elevated Levels of Plasmin-α2 Antiplasmin Complexes in Unstable Angina - Bayés-Genís, Antoni; Guindo, Josep; Oliver, Artur; Badimon, Lina; Fiol, Miquel; Mateo, Jose; Carles Souto, Joan; Dominguez, Jose M.; Fontcuberta, Jordi; Bayés de Luna, Antoni (Thrombosis and Haemostasis, 1999)
The evidence of elevated levels of several biochemical markers of prothrombotic state in patients with unstable angina suggests that thrombus formation and lysis play a pivotal role in acute coronary syndromes. The clinical syndrome of unstable angina encompasses a variety of clinical presentations of transient episodes of myocardial ischemia. This study was designed to assess plasmin generation in different settings of unstable angina. Evidence of plasmin generation in patients with unstable angina was measured by circulating plasmin-α2 antiplas-min complexes (PAP). A second objective was to identify whether PAP levels had a prognostic value to predict outcome. Eighty-five patients admitted to the coronary care unit for unstable angina were classified into three groups. Group A included 26 patients with postinfarction angina; group B comprised 26 patients with new onset angina; and group C included 33 patients with crescendo angina. Mean PAP levels were higher in the three groups compared to healthy controls. A significant correlation was found between levels of PAP and D-dimer, particularly in postinfarction angina (r = 0.6; p <0.0005). This trial adds new insights into the pathophysiology of unstable angina. It demonstrates that plasmin is generated in the different settings of unstable angina but particularly in postinfarction angina patients where a fibrin-rich thrombus is responsible of the symptoms. However, in this series PAP levels do not predict an uneventful outcome neither in the acute phase nor at long term (6 months).Abbreviations and acronyms: CABG: coronary artery bypass graft; CCU: coronary care unit; ECG: electrocardiogram; IABP: intraaortic balloon pump; MI: myocardial infarction; PAP: plasmin-α2 antiplasmin complexes; PTCA: percutaneous transluminal coronary angioplasty